Favorable response to PD-1 inhibitor plus chemotherapy as first-line treatment for metastatic gastric mixed neuroendocrine-non-neuroendocrine tumor: a case report - Lingnan Zheng; Lingqi Sun; Ji Ma (Frontiers Media S.A., 2024)
Gastric mixed neuroendocrine-non-neuroendocrine tumor (MiNEN), a rare malignancy, currently has no standard treatment. Here, we report a patient with pathologically confirmed gastric MiNEN following radical surgery with rapid postoperative distant tumor recurrence. Immunofluorescence results suggested intensive lymphocyte infiltration in the tumor. The programmed death receptor ligand 1 (PD-L1) immunohistochemistry 22C3 pharmDx assay showed tumor proportion score was 5% and combined positive score was 10. After 6 cycles of treatment with etoposide and cisplatin in combination with toripalimab, efficacy was assessed as a complete response. Our report shows that for gastric MiNEN patients with high expression of PD-L1, chemotherapy combined with immune checkpoint inhibitors may achieve more significant efficacy.